The effect of long-term whole-body vibration on muscular performance - Haleva, Yossef; Dunsky, Ayelet; Meckel, Yoav; Kleinöder, Heinz; Bar-Eli, Michael; Mester, Joachim (Brazilian Journal of Health and Biomedical Sciences, 2021)
Introduction: The whole-body vibration (WBV) approach is considered to be a unique training method for physical rehabilitation, injury preventions, and improving physical performance in athlete. The scientific literature about WBV is well documented and presents different vibration protocols, different measurements and, as a consequence - different results. Objectives: To explore the effect of a strengthening program with WBV on several muscular strength variables among physical education students in comparison to a control passive group of students. Methods: Thirty-eight healthy male physical education students were randomly allocated into Vibration Group (VG, n=13) - who underwent strengthening program with WBV and external load, and Control Group (CG, n=25), that received no treatment. The study included pre-test assessments, 4-week intervention phase and post-test assessments. During the intervention phase VG performed three training sessions per week that included six sets of 30 sec squats with external loads on a WBV platform. Assessments included maximal muscle strength, power, reactive strength and endurance. Results: Significant improvements were shown in all components among the VG from pre to post-tests (p<0.001), with no significant change among the CG. Conclusions: A 4-week strengthening program with WBV and medium external load improves different components of strength among healthy physical education students.